Recent Research in the Sahuaripa Region of Sonora, Mexico. Issue 4 (2nd October 2021) - Carpenter, John; Sánchez, Guadalupe; Hernández-Espinoza, Patricia Olga; León-Romero, Claudia Elena; Krug, Andrew R.; Abrego-Rivas, Alejandra; Shackley, M. Steven; Ferguson, Jeffrey; Pailes, Matthew
Abstract : This article summarizes research conducted in the Sahuaripa and Bacanora valleys of Sonora, Mexico. Located in the Serrana culture area of the Sierra Madre Occidental, data from this region speaks to several prevalent debates regarding the precolonial era of Northwest Mexico. Radiocarbon dates support demographic reconstructions for sizeable populations post-1000 AD; a time when other regions of the Northwest/Southwest (NW/SW) experienced significant demographic changes. Material cultural patterns reflect substantial local and regional connections with neighboring Río Sonora groups and Huatabampo. Recovered polychrome ceramics demonstrate long-distance connections with Casas Grandes, and obsidian data reflect connections to the Sonora and other neighboring valleys. These data indicate the Sahuaripa Valley participated in a corridor of exchange, which potentially included interaction between Casas Grandes and West Mexico. These observations are relevant to macro-scale patterns of interaction in the late-precolonial NW/SW.